Antiviral effect of ovotransferrin in mouse peritoneal macrophages by up-regulating type I interferon expression. Issue 1 (1st January 2018) - Zhou, Yulan; Tang, Qun; Du, Huaying; Tu, Yonggang; Wu, Shaofu; Wang, Wenjun; Xu, Mingsheng
ABSTRACT: Ovotransferrin (OVT) is one of the major proteins in avian albumen that exerts diverse biological activities. This study is aimed to investigate the antiviral effect and mechanism of OVT from the avian egg. Effects of OVT on vesicular stomatitis virus (VSV)-infected mouse peritoneal macrophage were detected by real-time quantitative polymerase chain reaction, enzyme-linked immunosorbent assay, and western blot. In OVT-pretreated mouse peritoneal macrophages, results showed that replication of VSV was significantly suppressed and production of type I interferon (IFN) was increased. OVT down-regulated ring finger protein 125 (RNF125) production and up-regulated retinoic-acid-inducible gene I (RIG-I) expression by the nuclear factor-κB signalling pathway, resulting in the enhancement of the production of type I IFN. It demonstrated that the antiviral effect of OVT on innate immunity is enhanced by promoting type I IFN expression, indicating its potential as a functional food ingredient.